Southeast Asian Peace Revisited: A Call for More Comprehensive Explanation - Purba, Elbinsar (Unnes Political Science Journal, 2024)
Many authors have tried to explain why Southeast Asia has been able to successfully maintain regional peace and stability. However, far from being able to provide convincing and commonly accepted answer, the current theories suffer from competing explanations and leave the puzzle unresolved. This paper explains the cause of this stalemate and finds that there are characteristics specific to Southeast Asia that collectively determine the nature of its transformation, namely diversity, colonial experience, culture of indeterminacy, and underdeveloped and non-complementary economy. As result of these characteristics, there are diverse factors that shape its peace evolution, there is no dominant driver of peace, and the region evolves incrementally. The paper argues that, in turn these lead to a serious methodological challenge for research on Southeast Asian peace. The paper concludes by offering some suggestions to overcome the challenge.